The Tribhum Image's Symbolic Motto in Thai Painting - Krongboon, Phornsawan; Pecharat, Dr.Chen (Journal of Dhamma for Life, 2023)
Traditional Thai painting is a painting related to Buddhism that has a particular style of writing that has been passed down for a long time since the Ayutthaya period, with a semi-ideal and semi-realistic character. Popular paintings tell stories in the Buddhist way, such as the Triphum, the Buddha's history, and the Jataka. As for the Tribhumi painting, there is a belief that appears to explain the realm from the lowest realm to the highest realm and the realm of Lokutara is the state that is freed from the cycle of the three realms. The painting depicts Mount Meru, which is believed to be the center of the universe, which is surrounded by the Sattabriphan Mountains, consisting of Yukonthorn, Isinthorn, Kravik, Suthatsana, Neminthorn, Vinattaka, and Atsa Mountains. Kan. The symbols of the four continents in the universe float on the Sithan River. The worlds where the heavens are situated ascend from the Brahma hierarchy to the Brahma forms, and the motto of explaining the consequences of evil deeds fall into the abyss. This is expressed in the image of the "hell landscape", the concept of Theravada Buddhist philosophy, believing in doing good deeds for the sake of the next world as the purpose of living and seeing the existence of the world. The picture talks about the duty that goes on as a cycle of karma for all beings, i.e. liberation from the cycle of suffering, that is, nirvana is the ultimate goal.